"IT’S UP TO YOU": WOMEN AT UBC IN THE EARLY YEARS. (Author: Lee Stewart) - Longacre, Judith (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 1991)
Lee Stewart. "IT’S UP TO YOU": WOMEN AT UBC IN THE EARLY YEARS. Vancouver: University of British Columbia Press, 1990. xii, 176 pp. 29.95, cloth; 19.95, paper.